SOME PHYSICO-CHEMICAL PROPERTIES OF SURIMI-LIKE MATERIAL MADE FROM GOAT MEAT AS AFFECTED BY SUCROSE LEVEL - Mega, O.; Suharyanto, S.; Badarina, I. (Diponegoro University, 2010)
This experiment was carried out to study the effect of sucrose level on the physico-chemicalproperties of goat surimi. The muscle tissue of round meat of goat was separated from fat andconnective tissue manually and then was cut into 3 cm size of meat for mincing by using meat mincer.Then, the minced meat was washed three times by using chilling water (5-10oC) which the final washingused chilled 0.5% NaCl solution. The ratio of water to minced meat in washing was 3:1. The final stepwas dewatering by pressing washed minced meat in the screen of linen mesh manually. Finally, rawsurimi was stirred with sucrose 3% (P1), 4% (P2) and 5% (P3) and added sodium tripolyphosphate 0.2%for each treatment. The result showed that both pH and Water Holding Capacity (WHC) increasedsignificantly from P1 (P<0.05), whereas the gel strength was no different. The incline of WHC wasfollowed by the incline of crude protein content. However, sucrose could not affect ash and fat contentas well as salt-soluble protein. Sucrose supplementation at 4% in goat surimi produced the bestcharacteristics of goat surimi.